Determinants of Performance Contracting Results in Kenya: A Case of Selected Ministries - Keter, Marystellah Nanjala; Mouni, Dr. Gekara (Journal of Public Policy and Administration, 2016)
Purpose: Performance Contracting is a contractual agreement to perform a duty in accordance to agreed-upon terms, in a specified time frame and with a predetermined use of resources and performance principles. It originated in France in the late 1960s .The main purpose of the study is to establish the determinants of performance contracting results in government ministries in Kenya. Methodology: The study used a descriptive research design. The target population of the study is Divisional heads, middle level managers and supervisors in 3 selected government ministries. These were Ministry of Education, Science & Technology, Ministry of Health and Ministry of Environment, Water & Natural Resources. Sample of 60 respondents was used. Results: Results shows that there is a positive relationship between performance contracting and leadership, human resource management, finance management, information system management as supported by beta coefficients of 0.107, 0.788, 0.050 and 0.225 respectively. Unique contribution to theory, practice and policy: Based on the finding the study recommends that the government should encourage the implementation of performance contracting in its ministries. This can be done through improving the leadership practices, human resource management practices, finance governance practices and information system management practices.